Vibrational Spectroscopic Investigation of Biomolecular Responses of Carbohydrate Structure to Moisture and Dry Heating in Soybean Seed (Glycine max) - Samadi, Samadi; Yu, P (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Abstract. The objective of this experiment was to investigate carbohydrate structures of seed tissue affected by different heat processing methods using infrared vibrational molecular spectroscopy. In this study, soybean seeds (two different harvested years; 2008 and 2010) were used as a model to investigate the alteration of inherent structure carbohydrate due to heat treatments. Structural characteristics of the bands in typical infrared molecular spectrum were studied in the region at ca. 1452-1188 cm-1 related to cellulosic and hemicellulosic compounds and the region at ca. 1193-881 cm-1, related to total CHO. Multivariate molecular spectral analyses: Hierarchical cluster analysis (CLA) and principal components analysis (PCA) were applied to identify heat-induced changes of molecular spectral profiles. Treatments used in this study were raw soybean seeds as control, autoclaved soybean seeds at 120°C for 1 h (HT-1: wet heating) and dry roasted soybean seeds at 120°C for 1 h (HT-2: dry heating). The results showed that the heat treatments did not change spectral profiles of cellulosic, hemicellulosic and total CHO. Based on spectral analysis, CLA and PCA also did not produce any alterations among different treatments in original spectra at cellulosic, hemicellulosic and total CHO regions. In conclusion, the molecular spectral technique with multivariate spectral technique can be considered as a research tool to investigate the magnitude of heat-induced change in carbohydrate molecular structure and other biopolymers in feeds, seed and plant tissues. These techniques could be used in the food and feed industry in which, losing or changing carbohydrate molecular chemistry was able to be detected in rapidly without any destruction and chemical hazardous. Further studies are needed to understand the trend in structural changes by heating with increasing temperature and time of exposure.Keywords: carbohydrate molecular, heat processing, molecular spectroscopy, soybean seed, feedsAnimal Production 14(1):23-31, January 2012